STUDY ON MALAYALAM SCRIPT - NANDINI JOSE (NATIONAL INSTITUTE OF FASHION TECHNOLOGY, 2013)
Kerala is witnessing a new wave – There is a huge appeal for products that combine the traditional and the contemporary. Particularly interesting are new trends that pay tribute to the roots, bringing back to light certain cultural elements that were once lost or forgotten. Methiyadi rubber footwear, inspired from ancient wooden padukas is a perfect example of this phenomenon. Avial – the band, fuses Malayalam folk and rock music in their music; the result – sound that the audience has never heard before but are familiar to in some way. Giving a new outlook to something local, while maintaining its essence is the ongoing trend. This new trend could be applied to the beautiful Malayalam script as well. The application of script as well should evolve with changing times, without stripping it of its essence. Malayalam lipi [script] is beautiful on its own; the loops, the swirls, the rounded turns. Although Malayalam script has been experimented with in the context of communication, it has not been explored much beyond that. To explore, an understanding of the origin, evolution and uses of the script becomes necessary. The objective of this research is to collect information about Malayalam script that would prove useful for anyone who hopes to use it in design. A qualitative research was conducted to understand the subject, through observation and by interviewing several artists and designers in the field. Through this research certain interesting things have come to focus – the need for archiving lettering and typographic works, new trends in design, increasing appreciation and importance given to the script, a changing market that is open to western concepts yet takes pride in their roots, and the huge scope that is there for products that include Malayalam script based designs.